2020
DOI: 10.1002/admi.202000191
|View full text |Cite
|
Sign up to set email alerts
|

Photonic Crystal Enhanced SERS Detection of Analytes Separated by Ultrathin Layer Chromatography Using a Diatom Frustule Monolayer

Abstract: Diatoms are single‐celled algae that biologically fabricate nanostructured silica shells with ordered pore arrays called frustules that resemble a 2D photonic crystal. A monolayer of Pinnularia frustules isolated from cell culture is deposited on a glass substrate and then conformally coated with silver nanoparticles (AgNPs) to serve as a nanostructured thin film for ultrathin layer chromatography (UTLC). Malachite green and Nile red are resolved in toluene mobile phase and the separated analytes are profiled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…Finally, monolayers of Pinnularia sp. frustules coated with silver nanoparticles have also been succesfully used in experiments based on the combination of SERS with ultrathin layer chromatography (UTLC) [101].…”
Section: Applications Of Diatom Frustules: Some Examplesmentioning
confidence: 99%
“…Finally, monolayers of Pinnularia sp. frustules coated with silver nanoparticles have also been succesfully used in experiments based on the combination of SERS with ultrathin layer chromatography (UTLC) [101].…”
Section: Applications Of Diatom Frustules: Some Examplesmentioning
confidence: 99%
“…A detailed investigation of the utilization of diatom frustules as substrates for the detection of different analytes has been recently shown by Kraai et al [75]. The group investigated the growth of silver nanoparticles (AgNPs) on the porous surface of Pinnularia sp.…”
Section: Diatoms As Surface-enhanced Raman Scattering (Sers) Platforms For Label-free Diagnosismentioning
confidence: 99%
“…Therefore, it is urgent to develop an alternative way that can bridge the coupling between the NIR-laser light and the optical properties of the assembled arrays. Photonic crystals with photonic bandgaps for enhancing the SERS performance have been flourished in recent years [34][35][36][37] , as the bandgaps can guide, localize and manipulate the incident light 31,35,38,39 . For example, Qi et al reported the TiO 2 inverse opal photonic crystal structure directly used as a SERS substrate.…”
Section: Introductionmentioning
confidence: 99%